Potential Regulatory Role in Mammalian Host Adaptation for a Small Intergenic Region of Lp17 in the Lyme Disease Spirochete - Crowley, Michael A.; Bankhead, Troy (Frontiers in Cellular and Infection Microbiology, 2022)
The bacterial agent of Lyme disease, Borrelia burgdorferi, relies on an intricate gene regulatory network to transit between the disparate Ixodes tick vector and mammalian host environments. We recently reported that a B. burgdorferi mutant lacking a transcriptionally active intergenic region of lp17 displayed attenuated murine tissue colonization and pathogenesis due to altered expression of multiple antigens. In this study, a more detailed characterization of the putative regulatory factor encoded by the intergenic region was pursued. In cis complemented strains featuring mutations aimed at eliminating potential protein translation were capable of full tissue colonization, suggesting that the functional product encoded by the intergenic region is not a protein as previously predicted. In trans complementation of the intergenic region resulted in elevated transcription of the sequence compared to wild type and was found to completely abolish infectivity in both immunocompetent "and immunodeficient mice. Quantitative analysis of transcription of the intergenic region by wild-type B. burgdorferi showed it to be highly induced during murine infection relative to in vitro culture. Lastly, targeted deletion of this intergenic region resulted in significant changes to the transcriptome, including genes with potential roles in transmission and host adaptation. The findings reported herein strongly suggest that this segment of lp17 serves a potentially critical role in the regulation of genes required for adaptation and persistence of the pathogen in a mammalian host.